Meta-Analysis: Effects of Lession and Exposed to Risk Factor on Leptospirosis Infection - Satriyo Fajar Wicaksono; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, 2023)
Background: Leptospirosis is a zoonotic disease that occurs due to interactions between agents, hosts, and the environment. Leptospira bacteria can infect humans through wounds on the skin and mucosa of the body. This study aims to examine the effect of injury history and contact risk factors on the incidence of leptospirosis by using meta-analysis. Subjects and Method: This was a systematic review and meta-analysis study carried out using the PICO model. P: Adults. Intervention: injury and contact. Comparison= no injuries and no contact with risk factors. Outcome: Leptospirosis. The meta-analysis was conducted by systematically reviewing articles from Google Scholar, PubMed, Springer Link, and Science Direct. Search keywords “Wound OR Lession AND Leptospira”, “Risk Factor Exposure AND Leptospira”, “Risk Factor AND Leptospira AND adjusted odds ratio”. The inclusion criteria used were full paper articles from 2002-2022 using Indonesian and English. The study design used was observational and the analysis used multivariate adjusted odds ratio results. Articles were collected using the PRISMA diagram and analyzed using the Review Manager 5.3 application. Results: Meta-analysis included 22 cross-sectional and case-control studies from Indonesia, India, Iran, Sri Lanka, Malaysia, Thailand, Laos, France, Germany, Kenya, Tanzania, Australia, Fiji, British Virgin Islands, Mexico, Jamaica, Peru, and Argentina. Leptospirosis increased with history of injury (aOR= 3.51; 95% CI= 2.94 to 4.19; p<0.001) and contact with risk factors (aOR=1.82; 95% CI=1.25 to 2.65; p=0.002). Conclusion: History of injury and contact with risk factors increases the risk of developing Leptospirosis. Keywords: history of injury, contact risk factors, leptospirosis, meta-analysis Correspondence:Satriyo Fajar Wicaksono. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: dr.satriyofw@student.uns.ac.id. Mobile: +6285641711987.